The transition from conformal to advanced radiotherapy techniques in the treatment planning of gynecological cancer patients - Petrović, Borislava; Ivanov, Olivera; Marjanović, Milana; Ličina, Jelena; Gencel, Ivan; Golubovac, Nemanja (Vojnosanitetski pregled, 2022)
Background/Aim. The transition from standard to highly conformal radiation therapy techniques requires the imple-mentation of complex advanced dosimetry. The aim of the study was to compare dosimetric parameters of the three-dimensional conformal radiotherapy (3DCRT) and volu-metric modulated arc therapy (VMAT) plan, as well as complications after treatment in relation to dosimetric pa-rameters in gynecological cancer patients. Methods. A total of 49 gynecological cancer patients were included in the study. All patients were planned for 3DCRT, but due to un-acceptable doses to organs at risk (OARs), treatment plans for intensity modulated radiation therapy (IMRT), or VMAT, were generated for 21 patients. The patients were prescribed 50.4 Gy/28 fractions (4 patients) and 45 Gy/25 fractions (45 patients). The coverage of planning target vol-ume (PTV) and doses to OARs were recorded. PTV mar-gins were evaluated for both techniques according to the Van Herk formula. Results. ICRU 83 criteria were fulfilled in all 3DCRT/VMAT/IMRT plans providing optimal cov-erage of PTV. Doses to OARs, on average, the V45Gy in the small bowel in IMRT/VMAT plans was four times smaller than the same in 3DCRT plans. The V45 Gy of small bowels was, on average, 49.4 cm3 in IMRT/VMAT plans, while in 3DCRT plans, it was 211.6 cm3. In the case of the femoral head, a significant reduction in V30Gy (10.8% vs. 33.1%) and mean dose in the case of IMRT/VMAT plans was recorded (30.4 Gy in 3DCRT vs. 23.6 Gy). Rectum was planned with a significantly lower dose in terms of V30Gy (79.5% vs. 95.2%) in IMRT/VMAT plans. The bladder was better spared in VMAT plans in terms of V40Gy (51% vs. 91%), but the maximum dose was higher in VMAT plans than in 3DCRT (50.1 Gy to 48.1 Gy on average). For all OARs, there was a statistically significant difference registered at p ˂ 0.05. Tox-icities recorded in VMAT and 3DCRT patients included mainly radiation-induced cystitis and enteritis. Patients treated with 3DCRT generally had longer recovery time. The homogeneity index was 0.11 for VMAT plans and 0.09 for 3DCRT plans. Conclusions. Analysis of dosimetric pa-rameters revealed significant differences in normal tissue doses for the same 3DCRT and VMAT patients, which confirmed the necessity for the implementation of advanced techniques for as many patients as possible.
Keywords: genital neoplasms, female; radiotherapy; radiotherapy, conformal; radiotherapy planning, computer-assisted; treatment outcome.